Recurrent pneumothoraces caused by a high-grade lung carcinoma with trophoblastic differentiation: a case report - Csaba, Márton; Megyesfalvi, Zsolt; Báthory-Fülöp, László; Pintér, Tamás; Agócs, László; Döme, Balázs; Rényi-Vámos, Ferenc; Ghimessy, Áron Kristóf (Frontiers in Oncology, 2024)
Gestational trophoblastic neoplasms are tumors that occur during pregnancy, while non-gestational trophoblastic tumors have a similar histology but are present outside of gestation. Literature reports several cases of non-gestational trophoblastic tumors of primary pulmonary origin, which pose diagnostic challenges and are associated with a poor prognosis. This report details a case of somatic high-grade carcinoma with trophoblastic differentiation primarily manifesting in the left lung with recurrent pneumothoraces. The tumor was initially diagnosed as a poorly differentiated pleomorphic carcinoma and was treated with paclitaxel and pembrolizumab, followed by the EMA-CO/EP regimen after the detection of liver, lung, and brain metastases. Despite initial treatment responses, the disease progressed with widespread metastases and severe complications, including myelotoxicity, empyema, and subarachnoid bleeding. The disease progressed rapidly, resulting in death within two years of diagnosis, highlighting the aggressive nature of this high-grade carcinoma with trophoblastic differentiation. Non-gestational trophoblastic tumors may represent a distinct disease group with unique clinical characteristics, and genetic analysis could help identify more cases.